2013
DOI: 10.1083/jcb.201212032
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of astrocytic laminin impairs vascular smooth muscle cell function and leads to hemorrhagic stroke

Abstract: Ablation of astrocytic laminin disrupted the interaction between vascular smooth muscle cells and astrocytes, down-regulated contractile protein expression, and weakened vascular integrity in deep brain regions, leading to hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 70 publications
4
92
0
Order By: Relevance
“…1b), suggesting that laminin expression is indeed abrogated in SMCs in SKO mice. Lack of laminin γ1 expression in nestin + cells has been validated before [10,19]. Here we showed that nestin + cells in NKO aorta were negative for laminin γ1 (white arrowheads, Supplemental Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…1b), suggesting that laminin expression is indeed abrogated in SMCs in SKO mice. Lack of laminin γ1 expression in nestin + cells has been validated before [10,19]. Here we showed that nestin + cells in NKO aorta were negative for laminin γ1 (white arrowheads, Supplemental Fig.…”
Section: Resultssupporting
confidence: 82%
“…F/F mice were crossed with SM22α-cre and nestin-cre transgenic mouse lines to generate F/F:SM22α-Cre + (SKO) and F/F:nestin-Cre + (NKO) mice, respectively. These knockout mice were born in the expected Mendelian ratios (data not shown), although NKO mice were smaller than their wild-type littermates [10]. The F/F and F/+ (heterozygous floxed laminin γ1) littermates were used as controls (Ctr).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to endothelial cells, specific subtypes of laminin are also produced by astrocytes and pericytes (Yao et al ., 2014). Previously, it has been shown that dysregulation in production of astrocytic laminin can compromise BBB by affecting pericyte differentiation and vascular smooth muscle cell function (Chen et al ., 2013; Yao et al ., 2014). Recently, by employing a high‐resolution MRI method, blood to brain transfer of gadolinium bound to plasma proteins (shows entry of large molecules that cannot usually enter the brain) was measured regionally in a quantitative manner.…”
Section: Discussionmentioning
confidence: 99%
“…100 In solid support of this notion, recent work revealed that genetic ablation of the laminin-g1 subunit in neurons and astrocytes disrupted astrocytic end-feet BM formation, consequently causing blood vessel disintegration and spontaneous hemorrhage in deep regions of the brain. 101 One could speculate that plasmin degradation of laminin or other components of the BM could inflict a similar effect.…”
Section: Conceptual Links Between Plasmin Activity and Blood-brain Bamentioning
confidence: 98%